(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
This article provides a detailed overview of the phases of the estrous cycle in cows, including their duration and clinical-biological signs. The physiological and external characteristics of sexual excitement, estrus (heat), ovulation, inhibition, and quiescence phases are described. Furthermore, synchronous and asynchronous estrous cycles are distinguished, and the difficulties in identifying them are discussed. The paper also analyzes the estrus discharge phenomenon, follicular status, changes in sexual receptivity, and the impact of these conditions on the reproductive health of cows. It emphasizes that proper evaluation and management of the estrous cycle can prevent infertility and improve breeding practices.